Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1128/aac.00234-23
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Iron-Transport Systems and β-Lactamases to Cefiderocol Resistance in Clinical Isolates of Acinetobacter baumannii Endemic to New York City

Abstract: The development of resistance to cefiderocol among multidrug resistant Acinetobacter baumannii has been attributed to downregulation in iron transport systems and a variety of β-lactamases. However, the precise contribution of each in clinical isolates remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Such a large repertoire of iron-acquisition systems in A baumannii implies an even larger repertoire of possible combinations of iron-acquisition systems, whose expression can be tuned according to the energetic status of the cell, the available iron source(s) and the physicochemical conditions of the growth environment. While the natural substrate specificity of the additional TonB-dependent receptors is still unclear, the piuA (DMO12_RS02620) and pirA (DMO12_RS05030) xenosiderophore receptors have recently been associated with the transport of cefiderocol, a siderophore–cefalosporin conjugate endowed with good activity on MDR P. aeruginosa and A. baumannii [ 67, 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a large repertoire of iron-acquisition systems in A baumannii implies an even larger repertoire of possible combinations of iron-acquisition systems, whose expression can be tuned according to the energetic status of the cell, the available iron source(s) and the physicochemical conditions of the growth environment. While the natural substrate specificity of the additional TonB-dependent receptors is still unclear, the piuA (DMO12_RS02620) and pirA (DMO12_RS05030) xenosiderophore receptors have recently been associated with the transport of cefiderocol, a siderophore–cefalosporin conjugate endowed with good activity on MDR P. aeruginosa and A. baumannii [ 67, 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all Bcc isolates with high cefiderocol MIC values belonged to the same species (i.e., B. multivorans ). Previous studies on cefiderocol susceptibility suggest that the presence of different resistance mechanisms, including mutations in iron transport-related proteins, defects in porin channels, and expression of certain β-lactamases, is needed to confer cefiderocol resistance in non-fermenter pathogens such as A. baumannii or P. aeruginosa ( 23 26 ). Thus, it may be possible that cefiderocol resistance in Achromobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…The transport of FDC from the outer membrane to the periplasmic space is mediated by passive diffusion via porin channels or active transport linked to TonB-dependent siderophore receptors PiuA and PirA [6] (Figure 1A). Thus, a positive correlation has been demonstrated between FDC susceptibility and the expression of PiuA and PirA TonB-dependent receptors (TBDRs) in A. baumannii [17,18]. Also, the high affinity of PiuA and PirA transporters for siderophores allows the transport of FDC in the periplasmic space even at low concentrations (Figure 1B) [19,20].…”
Section: Cefiderocol Is a Novel Siderophore Cephalosporin 21 Chemical...mentioning
confidence: 94%
“…FDC resistance has been associated with the reduced expression of the siderophore receptor pirA and piuA genes in several A. baumannii strains [17,18]. Also, Malik et al showed that two mutations in the midst of a beta strand of PirA diminished the functionality of this receptor protein in two FDC-resistant A. baumannii strains [17].…”
Section: Mechanisms Of Resistancementioning
confidence: 99%